(untitled) (Economic and Political Thought, 2019)
The aim of the article is to identify the main institutional weaknesses of Ukraine’s National Innovation System and to try to determine their consequences for the competitiveness of the Ukrainian economy in terms of international trade in high-technology and medium-high-technology goods, i.e. those created in industries based on knowledge and modern technologies. In other words, to examine whether and how Ukraine’s competitiveness in trade in these goods is changing in the face of the existing institutional weaknesses of its National Innovation System. In order to analyse the country competitiveness in international trade, B. Balassa’s method of analysing revealed comparative advantages was applied. The in-depth analysis of the dynamics of the revealed comparative advantages in Ukrainian exports in the years 2001–2016 clearly shows that the Ukrainian economy not only did not have any long-term comparative advantages in trade in high-technology and medium-high-technology goods in this period, but also its competitive position deteriorated in this respect. This should be attributed to strong institutional weaknesses within Ukraine’s National Innovation System, which significantly lower the effectiveness of this system and also reduce the ability to create and commercialise knowledge and innovation, as reflected in the lack of competitiveness of its economy in trade in high-technology goods.